Cochlear Implants for Patients With Common Cavity Deformities and the Impact of Electrode Positioning - Seong Hoon Bae; Jihoon Choi; Jae Young Choi (Clinical and Experimental Otorhinolaryngology, 2022)
Objectives Common cavity deformity is a rare congenital bony labyrinth malformation associated with profound hearing loss. Cochlear implants are widely used for hearing rehabilitation for common cavity deformities; however, the reported prognosis is poor. Due to the deformed anatomical structure, it is important to consider the position of the electrodes to maximize the performance of the cochlear implant. The present study discusses the impact of electrode placement on hearing outcomes. Methods A retrospective medical chart review of eight common cavity deformity patients (10 cochlear implants) who received cochlear implants was performed at a single university hospital. In all eight patients, implant surgery was performed using single-slit labyrinthotomy. Electrodes wer e manually bent before insertion to prevent misplacement and to reduce physical damage to the neuroepithelium. Results Four of the 10 electrodes were misplaced, with their tips placed in the anterior semicircular canal or internal auditory canal. However, after implant surgery, all patients—including those with misplaced electrodes—gained auditory perception and improved hearing function. One patient who had electrodes that did not contact the inner wall of the cavity showed limited activity of the electrodes (27%) compared to others (64%–100%). Conclusion Proper contact of the electrode with the inner wall was more likely to be important for cochlear implant success in cases of common cavity deformity than appropriate placement of the electrode tip.